International financial management - Madura, Jeff. (Thomson/South-Western, 2007)
This book combines a strong foundation in international finance theory with current, practical applications. It provides thorough, up-to-date treatment of cutting-edge international finance issues along with traditional coverage of international financial management. This book is known for its readability and clear explanations, as well as its extensive use of hands-on, real-world applications and reader-oriented pedagogy